Keterkaitan Transfer Pemerintah untuk Perlindungan Sosial terhadap Perilaku Merokok pada Rumah Tangga Miskin di Indonesia - Diyang Gita Cendekia (Jurnal Kependudukan Indonesia, 2018)
Indonesia has a relatively high proportion of the productive population. Decreasing the number consumption of cigarette is one of the ways to improve human capital, productivity, and wealth. The report published by Statistics Indonesia states that cigarettes expenditure is the second largest expenditure in poor households. On the other hand, poor households also get government social protection programs to help them get out of poverty. Therefore, this study aims to determine the association of the number types of social protection assistance programs received with smoking behaviour in poor households. By using multiple linear regression method, the results of this study found that the variables of the number types of social protection assistance received are related to the average of cigarettes consumed by the head of household in poor households. Besides, the study found that head of household in poor households who received three types of social protection assistance programs at once (Raskin, BLT and BSM) had a greater weekly average of cigarettes consumption than that of households in the same poor household that did not get any social protection assistance program